Organizational image, identity, and international divestment: A theoretical examination - WAN, William P. (Institutional Knowledge at Singapore Management University, 2015)
International divestment is a prevalent phenomenon and should be viewed as an integral part of the internationalization process. Nevertheless, the field of international business and strategy has paid scant attention to this topic. We develop a conceptual framework to examine a firm's propensity to divest internationally and the type of foreign operations it will divest. We posit that a firm's international divestment decisions are influenced by its organizational image and identity. Premised on this behavioral perspective, this article develops a theoretical model and generates a set of propositions to shed light on the topic of international divestment.